Artificial Intelligence and Social Ethics: Gandhian Approach - Shah, Neepa (Jaipur: Rawat Publications, 2024)
This book explores the multifaceted applications of Artificial Intelligence (AI) across various domains and its potential long-term societal implications. Over the past 50 years, spanning from the industrial era to the automation era, industries have undergone significant transformations. While such transitions have introduced benefits like increased efficiency, they have also raised concerns over unemployment, breach of privacy, shifts in human interactions, proliferation of high-tech weaponry, auto pilot vehicles, and more. Not only industrial sectors but domains including finance, security, healthcare, justice, entertainment, and education have also witnessed the integration of automated procedures, profoundly impacting human lives and catalyzing drastic societal transformations. Consequently, a virtual society is beginning to emerge alongside the real one, reshaping economies, politics, and cultures at both national and global levels. The foresight of Gandhian humanism anticipated these changes, foreseeing their potential harm to society. Gandhi$1 (Bs was not against machinery, but rather against its usage in manners that undermine human dignity and freedom. Gandhi$1 (Bs apprehensions regarding unemployment, the erosion of interpersonal connections, and the integrity of democracy resonate deeply in the context of our current era. His advocacy urged society to ready itself for the challenges of the present age and embrace community life.s
Keywords: Artificial Intelligence -- Machine Learning -- Deep Learning -- Cloud Computing; Social Ethics -- Ethics; Digital Automation; Gandhian Humanism